Destructive Production, Agroecology and Schools of Agroecology in Brazil - Novaes, Henrique Tahan, (Social Sciences E-Books Online, Collection 2025., 2025)
The debate on "sustainable development", ecosocialism, agroecology and the production of healthy food is increasing in Europe and in the world. This book depicts peasants' struggles for the resistance to the advance of destructive production. It also socializes the results of research, which shows us the pressage of alternative forms of labour, which are based upon agroecology, in cooperation and corporativism besides the emergence of agroecology schools of one of the main social movements of the present time: the Landless Movement.